COSMETICS ADVERTISEMENT LANGUAGE THROUGH DISCURSIVE PSYCHOLOGY - ARJULAYANA, ARJULAYANA; ENAWAR, ENAWAR (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
This paper looked into the language used in the advertisement of anti-aging cream based on a discursive psychology approach. The language used in the advertisement mainly raises the women's interest, especially when they hear the word